2021
DOI: 10.1245/s10434-021-10376-5
|View full text |Cite
|
Sign up to set email alerts
|

HIPEC-Induced Acute Kidney Injury: A Retrospective Clinical Study and Preclinical Model

Abstract: Background Hyperthermic intraperitoneal chemotherapy (HIPEC) combined with cytoreductive surgery (CRS) is the treatment of choice for selected patients with peritoneal malignancies. HIPEC is accompanied by moderate-to-high patient morbidity, including acute kidney injury. The significance of nephrotoxic agents such as cisplatin versus hyperthermia in HIPEC-induced nephrotoxicity has not been defined yet. Patients and Methods A total of 153 patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…As one of the serious complications in cancer patients, AKI has been proven to be associated with increased all-cause mortality and received great attention in clinical settings in recent years ( 20 , 21 ). Previous studies showed that the incidence of AKI after CRS plus HIPEC ranged from 1 to 48% ( 9 ). This vast variability might be related to the different ethnicities of the study population, and different chemotherapy protocols and doses applied in the treatment, besides, lacking consensus criteria of AKI might be another important reason for such a large variability of the incidence of AKI among those patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the serious complications in cancer patients, AKI has been proven to be associated with increased all-cause mortality and received great attention in clinical settings in recent years ( 20 , 21 ). Previous studies showed that the incidence of AKI after CRS plus HIPEC ranged from 1 to 48% ( 9 ). This vast variability might be related to the different ethnicities of the study population, and different chemotherapy protocols and doses applied in the treatment, besides, lacking consensus criteria of AKI might be another important reason for such a large variability of the incidence of AKI among those patients ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also data indicating that the application of CRS plus HIPEC has some non-eligible complications, and most causes of systemic toxicity of it are related to renal toxicity and bone marrow failure ( 7 , 8 ). The occurrence of acute kidney injury (AKI) in patients undergoing CRS plus HIPEC was also reported, and the incidence of it varied widely between 1% and 48%, the reason for the great variability in the prevalence of AKI might be related to different study populations, different regimens and doses for chemotherapy, besides these, the application of different definitions of AKI was also an important reason for that wide range of the AKI occurrence ( 9 ). Meanwhile, some associated risk factors for the occurrence of AKI like increased age, obesity, intraoperative blood loss, baseline renal dysfunction, preoperative hypoalbuminemia, and use of angiotensin-II receptor antagonists were identified among those patients ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Harnessing the excess RONS in renal system is an effective strategy for AKI treatment. Some small molecule antioxidants such as N-acetylcysteine (NAC), amifostine (AMF), and l -carnitine have been adopted in the adjuvant treatment of AKI [ [137] , [138] , [139] , [140] ]. However, these drugs have failed to become primary treatment for AKI owing to the low kidney targeting.…”
Section: Advantages Of Nanodrugs In Aki Treatmentmentioning
confidence: 99%
“…Additionally, the incremental activity of the sympathetic nervous system causes vasoconstriction of the splanchnic and renal circulation which combine with hypovolemia during HIPEC increases the risk of acute kidney injury. Interestingly, preclinical data suggest that hyperthermic perfusion itself does not aggravate HIPEC-induced acute renal failure and indeed is mostly the cytotoxic side effects of chemotherapy that causes the acute kidney injury in patients undergoing CRS-HIPEC ( 64 ).…”
Section: Biophysical Considerations Of Intra-abdominal Hyperthermiamentioning
confidence: 99%